Nasionalisme Masyarakat Perbatasan Republik Indonesia di Pulau Alor, Nusa Tenggara Timur - Siknun, Moh. Hikmatullah; Wardoyo, Broto (UI Scholars Hub, 2020)
Indonesia is currently experiencingdegradation of nationalism, it is indicated by the attitude of some of the younger generation who do not really appreciate national symbols, such as the Indonesia Raya song and the Red-White flag. One of the areas that has a level of vulnerability to the degradation of nationalism is communities who live in the border region, this is due to the location of the region which is very far from the center of government or it can be said that the region is closest to neighboring countries. The vulnerability of nationalism degradation in the border area of Indonesia can be seen from the case of the separation of Timor Leste from Indonesia. Alor Island, which is located directly neighboring to the Democratic Republic of Timor Lestehas strong national ties to this country due to their racial and ethnic similarities. The existence of these equations can encourage and influence the degradation of nationalism. This study aims to analyze the nationalism of the border society of the Republic of Indonesia on Alor Island, East Nusa Tenggara. Researcher used descriptive analysis method in this study. The results showed that the people of Alor Island are considered to have a strong attitude of nationalism but are still vulnerable to the degradation of nationalism. It is still necessary to maintain and even increase the nationalism of the Indonesian border society on Alor Island Keywords: Nationalism, Border Society, Republic of Indonesia, Alor Island